Design and construction of an Arduino-based load-shedding management system for improving electricity consumption in a medium-sized creative office building - Olumuyiwa Amusan; Benjamin Olorunfemi; Ayomide Fagboyo (Journal of Digital Food, Energy & Water Systems)
Standalone energy generation is revolutionizing electricity production and consumption by offering decentralized and sustainable options, benefiting communities, enhancing resilience, and reducing dependence on traditional power grids. Nevertheless, standalone electricity systems can face overloading issues when demand varies or exceeds capacity, necessitating careful control and adaptable solutions. The scalability of standalone electricity systems is limited by infrastructure, technology, and cost, hindering easy capacity expansion to accommodate higher loads. This paper explores the feasibility of managing load shedding in an office building with a standalone energy source, assessing its impact on optimizing electricity consumption and contributing to operational efficiency, sustainability, and resilience. A hardware prototype has been developed for a programmable interface designed to automatically manage various loads from the distribution board in a controlled manner. This includes controlling lighting, heating, cooling, security devices, and essential office gadgets. The system is implemented and validated through experiments utilizing the Arduino Mega control board. Operators can input load-shedding times flexibly using a 4x4 matrix keypad synchronized with the real-time clock (RTC). The microcontroller then instructs the relay to shed the specified load, displaying the shedding time on the LCD. The results indicate that the programmable interface exhibits a high dynamic response speed, highlighting its effectiveness and flexibility in load-shedding management. Comparing the cost of building the device with the long-term cost of overloading a standalone electricity generator, considering accelerated wear and tear, increased maintenance expenses, reduced operational lifespan, potential premature equipment failure, and overall decreased reliability, underscores the high-cost efficiency of adopting this device in office buildings. Additionally, implementing the system in an office building with an energy consumption of 23 kWh resulted in a discernible annual energy saving of 2.52 kWh by shedding off unnecessary loads at estimated timings.